Epinephelus adscensionis ... - Heemstra, P. C. (Zenodo, 1991)
Epinephelus adscensionis (OSBECK, 1765) Fig. 4. d Perca tota maculis... SEBA, 1758; 76, Pl. 27, Fig. 7 (type locality, unknown). Trachinus adscensionis OSEECK, 1765: 388 (type locality, Ascension Island, South Atlantic Ocean; holotype not located). Perca stellio WALBAUM, 1792: 349 (based on Perca tota maculis of SEBA). Trachinus osbeck LACEPÈDE, 1800: 364 (substitute for Trachinus adscensionis OSBECK; type locality, Ascension Island). Serranus pixanga VALENCIENNES, in Cuv. & VAL., 1828: 383 (type locality unknown [presumably Brazil]; based on a description by MARCGRAVE). Serranus nigriceps VALENCIENNES, m Cuv. & VAL., 1830: 517 (type locality unknown, holotype MNHN 7393 (264 mm.). Serranus impetiginosus MÜLLER & TROSCHEL, 1848: 665 (type locality, Barbados; holotype not located). Serranas capreolus POEY, 1860: 145 (type locality, Cuba; holotype not located). Serranus varius BOCOURT, 1868: 222 (type locality, Gulf of Mexico; holotype MNHN 5190 (166 mm)- Epinephelus adscensionis: See C. L. SMITH ... : Published as part of Heemstra, P. C., 1991, A Taxonomic Revision Of The Eastern Atlantic Groupers (Pisces: Serranidae), pp. 5-71 in Bol. Mus. Mun. Funchal 43 (226) on pages 17-20, DOI: 10.5281/zenodo.12168227 ...